1992
DOI: 10.2165/00019053-199201020-00008
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Safety, Timing and Cost-Effectiveness of Administering Antibiotics by Intravenous Bolus (Push) Versus Intravenous Piggyback (Slow Infusion) in Surgical Prophylaxis

Abstract: This study was carried out to evaluate the safety, timing and cost-effectiveness of administering perioperative antimicrobial prophylaxis with cefmetazole via intravenous (IV) bolus, or 'push', compared with the more common method of IV 'piggyback' administration. A total of 60 patients were studied, 30 in each group. No major adverse reactions were noted in either group. Phlebitis did not occur with either method of administration. Loss of patency was noted in 2 patients in the IV bolus group at the time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…One benefit is the reduced fluid volume needed to administer daptomycin. Other benefits of the bolus treatment are reported by Garrelts et al, such as optimal timing of administration and minimizing preparation and administration times [16]. That study compared the safety, timing, and cost-effectiveness of administering antibiotics by IV bolus versus IV infusion piggyback (slow infusion) in surgical prophylaxis [16].…”
Section: Discussionmentioning
confidence: 98%
“…One benefit is the reduced fluid volume needed to administer daptomycin. Other benefits of the bolus treatment are reported by Garrelts et al, such as optimal timing of administration and minimizing preparation and administration times [16]. That study compared the safety, timing, and cost-effectiveness of administering antibiotics by IV bolus versus IV infusion piggyback (slow infusion) in surgical prophylaxis [16].…”
Section: Discussionmentioning
confidence: 98%
“…1 3,14 When compared to IVPB antibiotic administration, Garrelts et al found that both pharmacy preparation time and nursing administration time were shorter in the IVP group. 15 By avoiding material costs, namely the minibag and intravenous tubing for IVPB, the researchers were able to demonstrate a cost avoidance of US$3.25 per dose. The extrapolated annual cost saving of the IVP method, for both treatment and prophylaxis, was US$184 000 in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The extrapolated annual cost saving of the IVP method, for both treatment and prophylaxis, was US$184 000 in this study. 15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 This technique of administering intravenous antibiotics has been determined to be safe, practical, reliable, and cost effective. [3][4][5][6][7] Significant cost savings have also been documented for other drug categories when intravenous bolus was used instead of intravenous infusion. 8, 9 The intravenous bolus method avoids the cost of minibags, infusion pumps, and administration tubing.…”
mentioning
confidence: 99%